Religious tourism and mass religious gatherings — the potential link in the spread of COVID-19. Current perspective and future implications - Mubarak, Naeem; Zin, Che Suraya (Elsevier USA, 2020)
COVID-19 has exposed the fragility and preparedness of healthcare systems around the globe. Various countries have widely adopted preventive measures, such as social distancing, face masks, frequent hand wash/sanitizer and lock downs. The pandemic with shifting epicentres from Wuhan to Iran and Italy presents two relevant questions for any next outbreak or epicentre in future: a) How did COVID-19 travel from one country to another? b) To what extent are countries prepared in context of preventive measures in mass gatherings in future?